Experimental and numerical study on post-fire behavior of high-strength Q460 steel columns. Issue 12 (December 2016) - Wang, Weiyong; Liu, Tianzi
Experimental study and finite element modeling on the structural behavior of high-strength Q460 steel columns after being exposed to ISO-834 standard fire are presented. Two section shapes were considered, namely welded H-shaped section and welded box-section. The experiment composes of two stages: heating and cooling stage of the specimens and compressive test on the specimen after fire exposure. The temperatures experienced in the specimens were recorded during both the heating and cooling phases, as well as the load–deflection curves, load–axial displacement curves, load–rotation curves, load–strain curves, and failure modes in the steel columns were measured during the compressive tests. Three-dimensional finite element models were also established by employing the program ANSYS to study the post-fire behavior of high-strength Q460 steel columns. The finite element models were used to investigate the effects of key parameters on the residual load-bearing capacity of high-strength Q460 steel columns, following exposure to the ISO-834 standard fire. The investigated parameters included heating time, cooling methods, and slenderness ratio. Finally, a simplified design approach was proposed for predicting the residual load-bearing capacity of high-strength Q460 steel columns after being exposed to ISO-834 standard fire.